2021
DOI: 10.1002/hep.31863
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte SH3RF2 Deficiency Is a Key Aggravator for NAFLD

Abstract: Background and Aims NAFLD has become the most common liver disease worldwide but lacks a well‐established pharmacological therapy. Here, we aimed to investigate the role of an E3 ligase SH3 domain‐containing ring finger 2 (SH3RF2) in NAFLD and to further explore the underlying mechanisms. Methods and Results In this study, we found that SH3RF2 was suppressed in the setting of NAFLD across mice, monkeys, and clinical individuals. Based on a genetic interruption model, we further demonstrated that hepatocyte SH3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Notably, Jin et al ( 2017 ) reported that loss of LBP can attenuate the development of WSD-induced NAFLD, which is inconsistent with our results. It is well established that the clinical pathogenesis and characteristics of NAFLD are highly heterogeneous ( Yang et al, 2021 ). Thus, different diets may trigger different hepatic pathological features, mimicking different clinical states of NAFLD, which may explain the different influences of LBP deficiency on NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Jin et al ( 2017 ) reported that loss of LBP can attenuate the development of WSD-induced NAFLD, which is inconsistent with our results. It is well established that the clinical pathogenesis and characteristics of NAFLD are highly heterogeneous ( Yang et al, 2021 ). Thus, different diets may trigger different hepatic pathological features, mimicking different clinical states of NAFLD, which may explain the different influences of LBP deficiency on NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is a major organ for systemic cholesterol and fructose metabolism, and recent studies have indicated that liver metastatic CRC cells have increased fructose and cholesterol metabolism, and genetically or pharmacologically inhibiting these metabolic switches could suppress liver metastasis of CRC [ 47 , 58 ]. NAFLD as a systemic metabolic stress enhanced DNL in hepatocytes via multiple mechanisms, such as upregulating of USP14 to deubiquitinate FASN and promote its stability, and depleting SH3RF2 to stabilize ATP citrate lyase (ACLY) [ 59 , 60 ]. In this study, we found that the NAFLD hepatic metabolic microenvironment could also enhance de novo palmitate biosynthesis in liver metastatic CRC cells and that enriched intracellular palmitate bioavailability could promote cancer cell stemness by facilitating palmitoylation of EGFR to promote its stability and PM localization.…”
Section: Discussionmentioning
confidence: 99%
“…The liver samples were collected from patients undergoing liver biopsy, liver surgery or liver transplantation. The exclusion criteria were described as follows: the male and female patients with drinking more than 140 or 70 g in a week respectively, using a drug or toxin with liver damage, viral infection or other liver disease were eliminated 27,28 . The study was authorized by the institutional ethics committee of Shandong provincial hospital and followed the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were described as follows: the male and female patients with drinking more than 140 or 70 g in a week respectively, using a drug or toxin with liver damage, viral infection or other liver disease were eliminated. 27,28 The study was authorized by the institutional ethics committee of Shandong provincial hospital and followed the Declaration of Helsinki. NAFLD activity score (NAS) following the roles: NAS ≥ 3 or 5 were sorted out as NAFLD and NASH respectively.…”
Section: Human Liver Samplesmentioning
confidence: 99%